2018
DOI: 10.1038/s41598-018-20367-4
|View full text |Cite
|
Sign up to set email alerts
|

Whole metagenome sequencing reveals links between mosquito microbiota and insecticide resistance in malaria vectors

Abstract: In light of the declining global malaria burden attained largely due to insecticides, a deeper understanding of the factors driving insecticide resistance is needed to mitigate its growing threat to malaria vector control programs. Following evidence of microbiota-mediated insecticide resistance in agricultural pests, we undertook a comparative study of the microbiota in mosquitoes of differing insecticide resistance status. The microbiota of wild-caught Anopheles albimanus, an important Latin American malaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
137
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(155 citation statements)
references
References 117 publications
8
137
0
4
Order By: Relevance
“…In the Sahelian region, 16 proteins involved in insecticide resistance, including thioredoxin, glutathione (GSH) peroxidase, GSH S‐transferase, cytochromes, ester carboxylesterase, enoyl‐CoA hydratase/isomerase, acyltransferase, and acetyl‐CoA carboxylase, [ 38,39 ] were up‐regulated in the cotton crops areas. Previous studies have shown that GSH S‐transferase, carboxylesterases and peroxidases were involved in the resistance to DDT and malathion, [ 38,40 ] while GSH S‐transferases and cytochromes were associated with resistance to DDT, permethrin, deltamethrin, λ ‐cyhalothrin, and malathion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Sahelian region, 16 proteins involved in insecticide resistance, including thioredoxin, glutathione (GSH) peroxidase, GSH S‐transferase, cytochromes, ester carboxylesterase, enoyl‐CoA hydratase/isomerase, acyltransferase, and acetyl‐CoA carboxylase, [ 38,39 ] were up‐regulated in the cotton crops areas. Previous studies have shown that GSH S‐transferase, carboxylesterases and peroxidases were involved in the resistance to DDT and malathion, [ 38,40 ] while GSH S‐transferases and cytochromes were associated with resistance to DDT, permethrin, deltamethrin, λ ‐cyhalothrin, and malathion.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41,42,43 ] Thioredoxin peroxidase was associated with resistance to deltamethrin [ 44 ] and acetyl‐CoA acyltransferase, enoyl‐CoA isomerase, and glutathione S‐transferase with resistance to organophosphate. [ 39 ] GSH S‐transferase and cytochromes were the most impacted by insecticide pressures in both climate regions. In An.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these new genera -Pluralibacter, Pseudocitrobacter, and Rosenbergiella -belong to the Enterobacteriaceae. Pluralibacter was recently differentiated from the Enterobacter genus (Brady et al, 2013) and was also found in the sand fly Phlebotomus chinensis Newstead (Li et al, 2016), the Mediterranean fruit fly (medfly), C. capitata (Papanicolaou et al, 2016), and the mosquito Anopheles albimanus Wiedemann (Dada et al, 2018). In contrast, Pseudocitrobacter and Rosenbergiella have never been reported as insect gut microbes before.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of the epithelium to gut microbiota during Plasmodium infection also triggers immune hemocyte differentiation (Rodrigues et al, 2010). Finally, elements of the microbiome may influence insecticide resistance phenotypes in mosquitoes (Dada et al, 2018). Thus, microbiome effects on mosquito vector biology may be multiple and important, but are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%